Karski : How One Man Tried to Stop the Holocaust - Wood, E. Thomas, 1963-; Jankowski, Stanisław M., 1945- (Book collections on Project MUSE., 2014)
""A novel focusing on the life of Uriah Philips Levy, the first Jewish commodore in the US Navy."--Provided by publisher"--